Mitigation of chemical wear by graphene platelets during diamond cutting of steel. (November 2016) - Chu, Bryan; Shi, Yunfeng; Samuel, Johnson
Abstract: The diamond cutting of transition metal alloys, particularly steel, is severely hindered by accelerated chemical wear of the tool. Recent experimental findings show that the presence of graphene platelets mitigates this problem. However, the specific mechanisms responsible for this wear mitigation are currently unknown. In this paper, molecular dynamics techniques are successfully used to identify these diamond tool wear mitigation mechanisms. A modified embedded atom method force field is first evaluated for its ability to accurately simulate the catalyzed graphitization of diamond in the presence of steel. This force field is then used to simulate nanometric diamond cutting of steel in the presence of a 1 or 3 layered graphene platelet. Coordination analysis of these simulations shows that the presence of the graphene platelet results in 34%–96% reduction in tool wear, when compared to the graphene-free cutting condition. This is attributed to the graphene platelet serving as a physical barrier protecting the tool cutting edge, and also as a sacrificial source for carbon transfer into the workpiece. Other mechanisms, such as platelet cleaving and interlayer sliding, are also observed. The reduction in tool wear reported by the simulations is comparable to the trends observed in prior experiments.